PEMANFAATAN MEDIA DIGITAL SEBAGAI STRATEGI KOMUNIKASI PEMASARAN PT. HARTADINATA ABADI, TBK. - Neng Alawiyah; Ida Riaeni (JIKE: Jurnal Ilmu Komunikasi Efek, 2025)
This Study is discusses the use of digital media as a marketing communications strategy at PT. Hartadinata Abadi, Tbk., a company engaged in the manufacture and distribution of gold jewelry in Indonesia. Digital media has become an important tool for reaching consumers more widely and efficiently in the era of digital transformation. The purpose of this study is to determine how the company utilizes digital media in developing its marketing communications strategy and to evaluate the effectiveness of this strategy. This research uses a qualitative descriptive approach with a case study method. Data were collected through in-depth interviews with marketing management, observations of the company's digital activities (including social media, websites, and e-commerce platforms), and related documentation. Data analysis was conducted using data reduction, data presentation, and conclusion drawing methods. The results show that PT. Hartadinata Abadi, Tbk. has integrated various digital media platforms such as Instagram, YouTube, and marketplaces to build brand awareness, increase consumer interaction, and support sales. This strategy has proven effective in increasing engagement and expanding market reach. The conclusion of this study is that digital media plays a significant role in supporting the company's marketing communications strategy. It is recommended that the company continuously evaluate the performance of digital media and optimize its utilization by following evolving consumer trends and behaviors. Keywords: digital media, marketing communications, marketing strategy, PT. Hartadinata Abadi, digital branding